PRODUCTIVITY OF THE GREENHOUSE TOMATO CULTURE IN THE LONG TURNOVER IN THE NORTH - T. К. Golovko; I. V. Dalke; G. N. Tabalenkova; R. V. Malyshev; E. E. Grygoray (Овощи России, 2018)
The data on the greenhouse tomato culture productivity in the long turnover (February November) without application of artificial light are presented. The plants were grown using small-volume hydroponic technology on mineral wool in the industrial greenhouse of LLC "Prigorodny" (Syktyvkar, 61° 40′ 35″ N, 50° 48′ 35″ E). Tomato seeds (hybrid Starbuck F1) were sown in early December 2016. The seedlings were illuminated for 19 h daily with the high-pressure sodiumvapor reflector lamps (HPSV-400W / REFLUX) with an installed power of 130 W/m2. In early February 2017 plants at the age of 4245 days were transferred to the greenhouse and grown at density of 2 plants per square meter under natural lighting conditions. The dependence between the light intensity at leaf level and the natural light entering the greenhouse was studied. In spring sunny days, the light intensity at the level of the upper leaves did not exceed the 450500 μmol quanta/m2s, and in cloudy weather was 2-3 times lower. It was found that the saturation of leaf CO2-uptake by light took place at intensity of 800-1000 μmol quanta/m2s. The leaves formed under light deficiency had lowered photosynthetic activity (near 3 μmol СО2/m2s). The maximal productivity of tomato culture was observed during maximum light levels and sunny period (June-July). The average value of tomato productivity was about 34 kg/m2. The data show the possibility of producing commercial tomato yield in the first light zone without artificial lighting, which significantly reduces production costs.